Behavioral restriction, lorazepam, and escitalopram uniquely influence the expression of naturalistic stereotypy in deer mice: perspectives on anxiety- and compulsive-like behavior - Burke, Johann T.; Mograbi, Daniel C.; Wolmarans, De Wet (Frontiers in Behavioral Neuroscience, 2022)
Stereotypical expression in laboratory-housed rodents can be explained by different motivational, coping, and motor dysfunction theories. Here, we aimed to explore the neurocognitive underpinnings of high stereotypical (HS) expression in deer mice (Peromyscus maniculatus bairdii), previously proposed as a model system of compulsive-like behavioral persistence. Specifically, we aimed to establish whether HS behavior is related to an underlying escape-related trigger. One-hundred and sixteen (116) deer mice were classified as either non-stereotypical (NS) or HS. Mice of each cohort were further subdivided and exposed to either sub-acute (3-day) or chronic (25-day) behavioral restriction (R), high-dose escitalopram (ESC), lorazepam (LOR), alone and in combination with R (ESC+R and LOR+R, respectively). Mice were reassessed for stereotypical behavior at both time points. Our results indicate that HS behavior is likely not temporally and functionally related to an anxiogenic trigger, i.e. R, but rather that HS is associated with parallel changes in anxiogenic feedback processing. We also show that chronic R alone significantly decreased the time spent in expressing HS behavior in animals of the HS, but not NS phenotype. This points to the possibility that HS-expressing mice represent a subgroup of P. maniculatus bairdii in which unique interactions between neurobiology and processes of gradual behavioral organization, may contribute to the expression of the typical behaviors observed in this cohort. Collectively, our findings highlight the value of the deer mouse model system to investigate the potential neurocognitive mechanisms that may underlie the development of persistent phenotypes that can likely not be explained entirely by current theories.